MANAJEMEN KURIKULUM PENDIDIKAN AL-ISLAM DAN KEMUHAMMADIYAHAN - syamsu Sanusi; Misran Misran (Kelola: Journal of Islamic Education Management, 2019)
The subjects of Al-Islam and Kemuhammadiyahan (AIK) are the terms of Islamic Religious Education courses applied to universities of Muhammadiyah which is very significant in forming students as professional, intellectual, and personal religious learning learner according to the guidance of Islam that upholds the value of humanity,and able to compete in the era of globalization, therefore the implementation process of AIK curriculum subjects must be well managed, structured and systematic. This research is qualitative descriptive, conducted in STKIP Muhammadiyah Palopo, aimed to describe the implementation of curriculum management of the subjects of al-Islam and Kemuhammadiayahan in STKIP Muhammadiyah Palopo. Data collection techniques used interview, observation, and documentation. Data analysis used data reduction techniques, data display, and conclusions. The results showed that AIK curriculum management functions in STKIP Muhammadiyah Palopo were well implemented, supported by muhammadiyah cadres and other stakeholders.